Highly Concentrated Electrolyte towards Enhanced Energy Density and Cycling Life of Dual‐Ion Battery - Xiang, Li; Ou, Xuewu; Wang, Xingyong; Zhou, Zhiming; Li, Xiang; Tang, Yongbing (Angewandte Chemie International Edition, 2020)
Dual‐ion batteries (DIBs) have attracted much attention owing to their low cost, high voltage, and environmental friendliness. As the source of active ions during the charging/discharging process, the electrolyte plays a critical role in the performance of DIBs, including capacity, energy density, and cycling life. However, most used electrolyte systems based on the LiPF6 salt demonstrate unsatisfactory performance in DIBs. We have successfully developed a 7.5 mol kg−1 lithium bis(fluorosulfonyl)imide (LiFSI) in a carbonate electrolyte system. Compared with diluted electrolytes, this highly concentrated electrolyte exhibits several advantages: 1) enhanced intercalation capacity and cycling stability of the graphite cathode, 2) optimized structural stability of the Al anode, and 3) significantly increased battery energy density. A proof‐of‐concept DIB based on this concentrated electrolyte exhibits a discharge capacity of 94.0 mAh g−1 at 200 mA g−1 and 96.8 % capacity retention after 500 cycles. By counting both the electrode materials and electrolyte, the energy density of this DIB reaches up to ≈180 Wh kg−1, which is among the best performances of DIBs reported to date. A 7.5 mol kg−1 LiFSI highly concentrated electrolyte was developed for a dual‐ion battery (DIB). A proof‐of‐concept DIB based on this concentrated electrolyte exhibits a discharge capacity of 94.0 mAh g−1 at 200 mA g−1, 96.8 % capacity retention after 500 cycles, and an energy density up to approximately 180 Wh kg−1 based on the electrode materials and electrolyte, which is among the best performances of previously reported DIBs.